Incidence and influencing factors of olfactory dysfunction in patients 1 week after endoscopic transsphenoidal resection of pituitary tumor: a cross-sectional study of 158 patients - Zhou, Sumei; Zeng, Zhi; Chen, Min; Zou, Linbo; Shao, Shirong (Frontiers in Neurology, 2024)
Objective To investigate the current situation of olfactory dysfunction in patients after endoscopic transsphenoidal resection of pituitary tumors, and analyze its influencing factors, to provide references for clinical nursing and rehabilitation. Methods A cross-sectional study design and convenience sampling method were used to investigate 158 patients with pituitary tumors treated by endoscopic transsphenoidal pituitary tumor resection in the Department of Neurosurgery of three Grade-A general hospitals in Sichuan Province from January 2022 and June 2023. The olfactory function of patients was evaluated 1 week after surgery, and the general clinical data and olfactory related data of patients were collected, and the influencing factors of olfactory disorder were analyzed by logistic regression. Results The incidence of olfactory dysfunction was 73.42%. analysis revealed that the formation of blood scabs, nasal cavity adhesion, cerebrospinal fluid leakage and operation time were independent risk factors for olfactory dysfunction in patients after transsphenoidal pituitary tumor resection (p < 0.05). Conclusion The incidence of olfactory dysfunction is high in patients after endoscopic transsphenoidal resection of pituitary tumors, suggesting that medical staff should pay close attention to and identify patients with olfactory dysfunction based on the guidance of disease knowledge and skills, develop targeted nursing interventions, and promote the improvement of patients’ olfactory function and quality of life.